The impact of adherence counseling incorporating a point of care urine tenofovir assay on virologic suppression among individuals failing tenofovir-lamivudine-dolutegravir: A pre-post intervention study - Leonard Bikinesi; Matthew A. Spinelli; Ntombizodwa Nyoni; Daniella Mouton; Assegid Mengistu; Jacques Kamangu; Iyaloo Konstantinus; Pearl Kalimugogo; Gram Mutandi; Fekir Negussie; Guohong Wang; Susie Welty; et al. (International Journal of Infectious Diseases)
Objectives: To examine if point-of-care (POC) urine tenofovir testing-informed counseling could be used to improve virologic suppression (VS) among participants with virologic failure (VF) after ≥1 prior round of enhanced adherence counseling (EAC). Methods: Participants were enrolled from 42 clinics across Namibia. At each monthly medication pick-up, participants completed the POC urine test and received EAC informed by this testing (EAC+). If VS was not achieved after 3 months of EAC+, up to 3 additional rounds of EAC+ were provided, with resistance testing at month (M)9. Results: Of 310 potentially eligible participants across 42 clinics in Namibia, we enrolled 211 participants with VF (median age 33 years, 61% female); 195 reached M3 defined as receiving EAC+ and follow-up viral load testing; 169 achieved VS within M3 (87%, P < 0.001) and 97% by M9 (181/186) compared to 40% (22/55) prior to the intervention (P < 0.001). Resistance testing was performed in five remaining participants with VF at M9, of whom 1/5 (20%) developed dolutegravir resistance. Conclusion: The urine tenofovir assay when incorporated into adherence counseling has potential to be a cost-effective intervention among participants failing tenofovir-based regimens, increasing VS to 97% in those failing Tenofovir-Lamivudine-Dolutegravir. Encouraging results of this pre-post intervention will be rigorously tested in a randomized trial.